Effect of antibiotics on gut microbiome diversity in Clarias gariepinus from commercial hatcheries - Durojaiye, Abiola; Sule, S.O; Oyetunji, O.T; Badewa, M.O (Acta Aquatica: Aquatic Sciences Journal, 2025)
The study investigated the effects of antibiotics on gut microbiome diversity in fish (Clarias gariepinus). Total aerobic count (TAC), total coliform count (TCC) and total fungal count (TFC) of gut contents were determined. Results revealed that there were significant differences (p<0.05) observed in the total aerobic and total coliform counts across the hatcheries. Using the Shannon and Simpson indices to measure variability in bacterial diversity among the hatcheries, TAC in hatcheries using antibiotics had greater diversity compared to hatcheries not using antibiotics while TCC where hatcheries not using antibiotics had higher diversity than the ones using antibiotics. This indicates that hatcheries where antibiotics were not used had higher microbial densities than hatcheries where antibiotics were used.  However, it was observed that fungi were completely absent as indicated in the total fungal counts. In hatcheries using antibiotics, Shigella spp, Klebsiella spp and Salmonella spp were isolated while in hatcheries not using antibiotics, Shigella spp, Klebsiella spp and Enterobacter spp were isolated. Sorensons coefficient indicated a slight overlap or similarity with a value of 0.667 among the bacterial communities in samples from farms using antibiotics and ones not using antibiotics. All the bacteria isolated belong to the phylum Proteobacteria. The study revealed that antibiotics had a slight effect on the diversity of the fish gut microbiome indicating that antibiotics are moderately used in fish hatcheries in Ijebu-Ode Region of Ogun State.Keywords: Antibiotics; Diversity; Gut Microbiome